The Annales School and the Environmental History of Latin America - Tortolero Villaseñor, Alejandro (Historia Caribe, 2017)
There are different influences in Environmental Latin-American History. From the historical demography to anthropology, this discipline has been benefit from Cook and Borah’s contributions to Carl Sauer’s. In this article, my contribution consists in broading the spectrum towards the European influence and particularly to the so-called Annales School. While it is true that this movement had a strong influence in Latin-American History, in contrast, in Environment Historians, such influence has not been comparable to quantity history or the history of prices. My purpose is to analyze the roots of this influence in Latin America, their scope and limits.